Stressors in nursing professionals working in critical hospital areas (Revista Innova Educación, 2021)
The objective was to identify stressors in the nursing professionals who work in critical areas of Hospital III in Essalud Puno (Peru). The type of research was descriptive cross-sectional comparative where 45 professionals participated. The instrument applied was the Nursing Stress Scale (NSS) that measures stressful situations in the nursing professional. The results indicate that the factors appear in the physical, psychological and social environment. The most affected was the physical environment, considering the workload at 28.9%. In the psychological environment, lack of support was observed in 28.9%, uncertainty in treatment with 24.4%, insufficient preparation in 17.8%, and death suffering in 16.7%. In the social environment the problems with the doctor is 28% and with other members (nurse or others) 17.8%. Comparing the critical areas in the Essalud III hospital, there are frequently stressors in the areas of the Intensive Care Unit - Intermediate Care Unit, neonatology, emergencies and the surgical center. It was also evidenced that marital status affects single women in the physical environment in 31.8%, in the psychological environment in married women in 20.7%. According to the years of service, the most affected are the professionals who had 21 to 25 years of service in 100.0% and from 21 to 25 years reported stress in the physical environment in 66.7%.
Keywords: stressors; critical areas; tasks; Nurse; hospital